2020
DOI: 10.18280/ijdne.150417
|View full text |Cite
|
Sign up to set email alerts
|

Land Index and Production of Arabica Coffee (Coffea Arabica L.) in Smallholding Plantation of Tana Toraja District, Indonesia

Abstract: This study aimed to evaluate the suitability of Arabica coffee plantations and analyze the relationship between land suitability index and Arabica coffee production. This study used quantitative methods conducted by direct surveys in Arabica coffee plantations in Tana Toraja District, South Sulawesi. The analysis of land suitability was performed using a parametric approach with the Storie Index equation. Then it followed by an analysis of the correlation between land suitability index and Arabica coffee produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Off-farm employment and part-time employment can significantly affect the scale of land transfer of farmers [16,17]. Some scholars' studies show that the larger the leased area of farmland, the larger the operation scale, the higher the profit [18][19][20], the more obvious the income effect, and the more possible income of transferees' [21]. In relation to government subsidies, scholars generally believe that subsidies are the most effective policy tools to promote the transfer of farmland and improve the income of transferees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Off-farm employment and part-time employment can significantly affect the scale of land transfer of farmers [16,17]. Some scholars' studies show that the larger the leased area of farmland, the larger the operation scale, the higher the profit [18][19][20], the more obvious the income effect, and the more possible income of transferees' [21]. In relation to government subsidies, scholars generally believe that subsidies are the most effective policy tools to promote the transfer of farmland and improve the income of transferees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This indicates that medium elevation farm provides the most optimum environmental conditions for coffee production. The studies [6,50] reported that air temperature in the coffee farm is one of the most influencing factors in Arabica coffee production. In low altitude areas, the Borbor variety shows better adaptation and is more resistant to CBB attacks.…”
Section: Interactive Effect Of Farm Altitude and Varietymentioning
confidence: 99%
“…Therefore, there is a need for the introduction of technology to improve coffee farming. This recommended technology introduction encompasses various aspects, including the selection of planting materials, the application of fertilizers, weed management, pest and disease control, harvesting, post-harvest production, and the marketing of coffee beans [12] [13].…”
Section: Introductionmentioning
confidence: 99%